Hydrodynamics and measurement of natural currents in a plain river using acoustic Doppler equipment - Priego-Hernández, Gaston; Rubio-Arias, Héctor; Rivera-Trejo, Fabián (Ecosistemas y Recursos Agropecuarios, 2018)
Flow discharge and hydrodynamic field measurements are essential data for understanding aquatic ecosystems. The objective of this study was to compare the use of three Acoustic Doppler Current Profilers (ADCPs) in measuring flow discharge and hydrodynamics in the Carrizal River located in southeastern Mexico. The evaluated ADCPs operate on frequencies of 2 000 kHz, 1 500 kHz and 600 kHz. The measurements were carried out in a 100-m-wide cross section, five times each for each ADCP, within an estimated time of 5 min. The obtained data were: 1) flow velocity components; 2) depth; 3) transversal distance between each vector; 4) total distance of the cross section and; 5) geographic position of each vector. Tecplot® graphics were made with the collected information. The results showed that velocity magnitudes were low in bank areas, while high in the center. For a 5-m depth range, the 2 000-kHz ADCP keeps a more homogenous velocity distribution in comparison with the other equipment. The results showed that discharge measurements varied by no more than 5% among ADCPs. It is concluded that the most important variable in choosing an ADCP for a hydrodynamic study is its operating frequency